Self-Cleaning Performance of Basalt Fiber-Reinforced GGBS-Based Geopolymer Mortar Containing Nano TiO2 - Tanyildizi, Harun; Yilmaz, Atilla; Acik, Volkan; Demirelli, Kadir (Asce-Amer Soc Civil Engineers, 2024)
This study examined the self-cleaning and mechanical properties of basalt fiber-reinforced ground granulated blast furnace slag (GGBS)-based geopolymer mortar containing nano TiO2. The nano TiO2 and basalt fiber in mixtures were used at 0%, 0.25%, 0.5%, and 1% by weight of GGBS. The cubes (50x50x50 mm) and prisms (40x40x160 mm) samples containing nano TiO2 and basalt fiber were produced and cured in the oven for 24 h at 60 degrees C. Then, these samples were kept at room temperature at 23 degrees C +/- 2 degrees C for 28 days. Lastly, the compressive strength, flexural strength, ultrasonic pulse velocity, capillary water absorption, and self-cleaning tests of GGBS-based geopolymer mortars were carried out. In this study, the Rhodamine-B test was used to determine self-cleaning. This study showed that the compressive strength, flexural strength, and ultrasonic pulse velocity values of the GGBS-based geopolymer mortars increased as the nano TiO(2 )and basalt fiber ratios increased, but their capillary water absorption coefficient decreased. Also, this study found that the self-cleaning rate of GGBS-based geopolymer mortars containing 1% nano TiO2 was obtained as 50.62% at 28 days.
Keywords: Ground granulated blast furnace slag (GGBS)-based geopolymer mortar; Nano TiO2; Basalt fiber; Mechanical properties; Self-cleaning; Cost analysis